Análise dos efeitos do sal perclorato de lítio sobre o desempenho de transistores com porta eletrolítica à base de mel - Patrzyk, Jéssica Nayara (2024)
This work explored the use of electrolyte-gated transistors (EGTs), using honey as the electrolyte layer, focusing on the influences that lithium perchlorate salt added to honey has on EGT’ electrical behavior. This investigation shows the potential of using the honey-gated transistors (HGTs) applied as a sensing platform, where the salt simulates a possible analyte to be detected. EGTs can present two different modes of operation, depending on the voltage range used on the gate electrode: as Electrolyte-Gated Organic Field Effect Transistors (EGOFET) when its modulation occurs due to the field effect that induces charges into channel; or as Organic Electrochemical Transistors (OECT) when ions drift into the channel resulting in ionic doping. The literature in the area had already shown that HGTs only present the EGOFET operating mode. This work showed that the use of lithium perchlorate together with honey created HGTs operating in OECT mode, where the channel is doped by the ClO− 4 anion, changing its electrical properties observed in the transfer and output curves. This process becomes reversible when a reverse voltage is applied to the gate electrode, in order to promote channel dedoping. This doping and dedoping control is fundamental for using this platform as a sensor. Furthermore, two different mechanical matrices were tested for anchoring the honey electrolyte. Honey is a viscous electrolyte and, controlling and manipulating it is not simple. Bond paper and sheet gelatin were tested as an anchoring matrix, both acquired at extremely low cost in common market, not intended for laboratory applications. Paper anchoring proved to be very efficient, not promoting significant changes in the EGT’s operating modes, in relation to the situation without an anchoring matrix. The use of this array is also an important step towards extending the use of this EGT as a sensing platform. This occurs because the matrix allows the analyte to be deposited away from the active area of the EGT by any non-specialized person, where the ionic liquid is absorbed along the matrix reaching the transistor to carry out the measurement. This set of results shows the potential of honey-gated transistors to be applied as a sensing and biosensing platform, since honey is a biocompatible, antifungal and antibacterial material.